Improving Early Qur’an Reading Skills Through the Ummi Method and Structured Learning Management - Delsi Susanti; Nenny Mahyuddin; Yaswinda Yaswinda; Dadan Suryana (Journal of General Education and Humanities, 2026)
The low level of Qur’an reading proficiency among early childhood learners highlights the need for effective instructional methods supported by appropriate learning management. This study aims to analyze how the Ummi method, integrated with learning management practices, contributes to the improvement of early childhood Qur’an reading skills at Tahfidz Al-Ihsan Kindergarten. Unlike previous studies that primarily focused on the effectiveness of the Ummi method itself, this research examines the combined role of instructional management, including planning, implementation, learning strategies, media utilization, and evaluation processes. The study employed a mixed-methods approach using a sequential exploratory design, in which qualitative findings were used to explain and strengthen quantitative results. The participants consisted of 15 kindergarten students. Data were collected through observations, interviews, documentation, and pretest-posttest assessments of Qur’an reading ability. Quantitative data were analyzed using a paired sample t-test, while qualitative data were analyzed descriptively through data reduction, presentation, and conclusion drawing. The findings indicate that structured learning procedures, repetition-based practice, direct instruction, affective approaches, and continuous evaluation supported the implementation of the Ummi method. Quantitative results showed an increase in the mean score from 42.87 on the pretest to 89.80 on the posttest. The paired sample t-test revealed a significant difference between pretest and posttest scores (p < 0.001; t = 17.794), with a very large effect size (d = 4.594). These findings suggest that the integration of the Ummi method and systematic learning management has the potential to support the development of early childhood Qur’an reading skills within the studied context.